Antioxidant capacity in microorganisms causing clinical and subclinical mastitis in raza carora mestized cows and its relationship with the electronic counting of somatic cells (Gaceta de Ciencias Veterinarias, 2023)
The bacterium in mammary gland raise CS, 90% are neutrophils with a phagocytic function, releasing enzymes, inflammatory mediators and reactive O2 species. Superoxide dismutase (SOD-CuZn) counteracts these species, produced by white milk cells. The objective of  the study was to determine the SOD in bacteria that cause clinical and subclinical mastitis. Selected 20 Carora-Holstein cows with mastitis in the first 20 days postpartum: 15 with subclinical mastitis and 5 with clinical mastitis, the first determined by the California test, confirmed by electronic SC count and clinical mastitis with the black background test, before milking. Once the bacterial strains were identified, the SOD was measured in U/mL. 6 Staphylococcus strains were isolated, whose SOD was 46.27±5.08; 4 strains of Pseudomonas aeruginosa with 139.59±4.73; 3 strains of Bacillus sp with: 36.24±0.71; 2 strains of Streptococcus uberis with 39.01±0.71; 2 strains of Streptococcus dysgalactiae with 23.54±0.38; 2 strains of Corynebacterium sp with 117.92±0.71 and 1 strain of E. coli with122.43. The results indicate that Pseudomonas aeruginosa, Corynebacterium sp and E. coli have a higher activity of SOD, which wouldi ndicate that they have an efficient antioxidant system to avoid the respiratory burst of white milk cells, favoring the evolution of the inflammatory process in the mammary gland.
Keywords: SOD; mastitis; bacterias; Carora cows